Arm lymphoedema after axillary surgery in women with invasive breast cancer. Issue 4 (March 2014) - Sackey, H.; Magnuson, A.; Sandelin, K.; Liljegren, G.; Bergkvist, L.; Fülep, Z.; Celebioglu, F.; Frisell, J.
<x xml:space="preserve">Abstract</x> Background The primary aim was to compare arm lymphoedema after sentinel lymph node biopsy (SLNB) alone versus axillary lymph node dissection (ALND) in women with node‐negative and node‐positive breast cancer. The secondary aim was to examine the potential association between self‐reported and objectively measured arm lymphoedema. Methods Women who had surgery during 1999–2004 for invasive breast cancer in four centres in Sweden were included. The study groups were defined by the axillary procedure performed and the presence of axillary metastases: SLNB alone, ALND without axillary metastases, and ALND with axillary metastases. Before surgery, and 1, 2 and 3 years after operation, arm volume was measured and a questionnaire regarding symptoms of arm lymphoedema was completed. A mixed model was used to determine the adjusted mean difference in arm volume between the study groups, and generalized estimating equations were employed to determine differences in self‐reported arm lymphoedema. Results One hundred and forty women had SLNB alone, 125 had node‐negative ALND and 155 node‐positive ALND. Women who underwent SLNB had no increase in postoperative arm volume over time, whereas both ALND groups showed a significant increase. The risk of self‐reported arm lymphoedema 1, 2 and 3 years after surgery was significantly lower in the SLNB group compared with that in both ALND groups. Three years after surgery there was a significant association between increased arm volume and self‐reported symptoms of arm lymphoedema. Conclusion SLNB is associated with a minimal risk of increased arm volume and few symptoms of arm lymphoedema, significantly less than after ALND, regardless of lymph node status.